(untitled) (Al-Academy, 2018)
The research consisted of four chapters, the first of which wasa methodological framework. The problem of research was determined by a question drawn up by the researcher as follows: What are the intellectual contents of science fiction films ?. The main objective of the research was to uncover the intellectual contents of contemporary science fiction films. The most important research terms (content, thought, ideology, science fiction, contemporary) were defined as either the second chapter (the theoretical framework) The second topic was entitled "The Intellectual Contents of Contemporary Science Fiction Films", in which the films of the science fiction and its current intellectual contents were discussed. The third topic included the "Transformations of Characters in Films" Fantasy J), with the focus on the personal in some science fiction movies and set covered at the level of intellectual perspective and Alabestmaologi. The third chapter (research procedures) included the community, methodology, sample and research tool, and sample analysis via the model (Super 8) 2011 by director (GJ Abrams). In the fourth chapter, the researcher reached conclusions, conclusions, suggestions and recommendations, followed by a list of sources and a Abstract in English.